Dayak Sape' Music Workshop as a Medium for Cultural Communication, Skill Development, and Appreciation of Nusantara Music - Rahmat Kurniawan; Sri Riski Wulandari; Andi Zulfikar Alam (Yayasan Ahmar Cendekia Indonesia, 2025)
The Dayak Sape' is a significant intangible cultural heritage of Indonesia, yet it faces challenges in the modern era. This Community Service Program (PKM) aims to utilize Sape' music training as a medium for communicating Dayak culture, developing multidimensional skills (musical, motor, cognitive, social), and fostering appreciation for the diversity of Nusantara music. Through a comprehensive literature review and the design of a hypothetical training program involving participatory learning, technical practice, and cultural discussions, this article examines the' potential of the Sape'. Analysis indicates that Sape' training effectively transmits Dayak cultural knowledge and values, develops musical, fine motor, cognitive (memory, concentration), and social (collaboration, self-confidence) skills, and enhances appreciation for Sape' music and other rich Indonesian traditional music. This program holds significant importance for cultural preservation, community empowerment, and holistic education rooted in local wisdom.